INTRODUCTION OF CULTURE THROUGH CHILDREN'S LITERATURE THE LITTLE BEADS ON MY DRESS: STYLISTIC STUDY - Zamruddin, Mardliya Pratiwi; Nasir, Muhammad Alim Akbar (Fakultas Ilmu Budaya, Universitas Mulawarman, 2023)
This study describes the style of language used in the children's story The Little Beads on My Dress. This research is a qualitative descriptive study which aims to explain the style of language used in the children's story. The style of language that will be analyzed is the style of language from the aspect of story structure that occurs in the story and is associated with efforts to introduce the culture of one of the tribes in Indonesia, namely the Dayak Bahau tribe. The events that occur in the children's literature are imaginative works by the author which are told to occur in a village that actually exists in Indonesia, just as the traditions that are told in the story are also original traditions carried out by the Dayak Bahau tribe.